Literary Traditions: English in Malaysia and Singapore (Column 1) - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2014)
The young editors of a student magazine, The New Cauldron (1949-60), the official organ of the Raffles Society of the University of Malaya in Singapore, in their youthful idealism and unflagging optimism, wrote in their editorial column, “National Unity,” for the Trinity Term issue of 1949-1950: Professor T.H. Silcock, in his pamphlet 'Dilemma in Malaya', says that 'Self-government implies a self to do the governing, and it is our responsibility to bring that self into existence.' Before that 'self' can emerge we must have a solidified concoction of all the socially, economically, politically and culturally disunited peoples in Malaya. Can we achieve that solidarity? Assuredly we can. The process of transforming different peoples with diverse ideas into a single unit may take a few decades but ultimate unity is ours. The rest of the editorial is devoted to articulating the principles that would enable the emerging nation to attain the desired unity: equality of races and equal citizenship for all, for “There is no room for discrimination in a ship upon turbulent waves of suspicion”; undivided loyalty to Malaya, particularly by members of the migrant races and, finally, the evolution of a common language. On the subject of language, the starry-eyed editors further wrote, in their editorial article, “The Way to Nationhood,” for the Hilary Term issue of 1949-1950: The people of Malaya are a mixed crowd, but they possess most of the requisites for nationhood. Time must be given for a common language to be evolved. This will come about through increased contact between the different communities. A Malayan language will arise out of contributions these communities will make to the linguistic melting pot. The emerging language will then have to wait for a literary genius who will give it a voice and a soul, a service which Dante performed for the Italian language.